PASSAGE INFLUENCE ON THE AGING PROFILE AFTER SUCCESSIVE CRYOPRESERVATION OF BONE MARROW MESENCHYMAL STEM CELLS - Ismail Hadisoebroto Dilogo; Starifulkani Arif; Jeanne Adiwinata Pawitan; Ria Anggraeni; Yogi Ismail Gani (Journal of Global Pharma Technology, 2017)
Objective: Bone marrow mesenchymal stem cells are promising in cell therapy but the low frequency of this subpopulation necessitates their in vitro expansion and cryopreservation prior to clinical use. The aim of this study was to analyze the passage effect on the aging profile of previously successive cryopreserved bone marrow mesenchymal stem cells.  Methods: The samples of this in-vitro observational analytic study (April - September 2016) were iliac crest bone marrow mesenchymal stem cells that were cryopreserved in passage one and a second group was cryopreserved after being subcultured. It was obtained from UPT TK Sel Punca RSCM-FKUI. Samples were analyzed for each passage in terms of cell size, viability, population doubling time (PDT), and percentage of senescent cells by ANOVA test and independent t-test for the inter-cryopreservation group.Results: The remarkable manifestation of senescence appeared at passage six in both cryopreserved groups, but tend to appear earlier in the twice cryopreservation group. The senescent positive cell size became bigger along with the increasing number of passage. There were significant differences in PDT, 30% confluent cell size, viability, in passage six between the two cryopreservation groups (p<0.001, p<0.001, p=0.022), respectively, but no significant difference in percentage of senescent cells (p= 0.052). The cells became senescent in P6 in both groups (P=0.000).Conclusion: The onset of senescence of bone marrow mesenchymal stem cells was in passage six, while PDT, cell size and viability differ significantly due to successive cryopreservation.